Peran Pengorganisasian di Sekolah dalam Manejemen Bimbingan dan Konseling - Aditia Kharisma Meliala; Uman Suherman; Fadhil Muhammad (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The purpose of the study was to determine the role and tasks of the school organisation in the management of Guidance and Counselling. Organisational climate is a form of situation that occurs in an organisation that is formed by relationships between individuals. Many teachers complain about the discrepancies within their school hierarchy. For the school organisational environment to thrive and survive, mutual guidance is needed to create a supportive and effective environment. This research uses literature review research. Nazir (2003), revealed that literature research is a data collection technique by conducting a study of books, literature, records, and reports that have to do with the problem to be solved. In conclusion, the author recommends that school principals, understand the main tasks and functions of counsellors well and carefully, provide facilities and infrastructure for Guidance and Counselling teachers, so that Guidance and Counselling activities can be carried out properly. For subject teachers, they should collaborate with Guidance and Counselling teachers in socialising Guidance and Counselling services and participate in identifying students who are experiencing problems and help collect important information related to students' personal data.